1977
DOI: 10.1039/p19770001718
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of relevance to the chemistry of aminoglycoside antibiotics. Part 7. Conversion of thiocarbonates into deoxy-sugars

Abstract: Radical-initiated reduction of five-or six-membered ring thiocarbonates, followed by alkaline hydrolysis, affords a convenient synthesis of 2-, 3-. 4-, and 5-deoxy-sugars. For 5,6-and 4.6-thiocarbonates the regiospecificity of the reaction complements the recently developed synthesis of 6-deoxy-sugars by ring opening of the same thiocarbonates with methyl iodide. Applications in the synthesis of 2-deoxy-~-ribose and 2'-deoxyadenosine are described.WE recently reported1 that the thiocarbonate ring in compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 0 publications
0
27
1
2
Order By: Relevance
“…Forma-se exclusivamente o produto C-5-desoxi 59. Esta seletividade é atribuída à maior estabilidade do radical secundário (em C 5 ) quando comparada a do radical primário (em C 6 ) (Esquema 17) 84,98,99 .…”
Section: Desoxigenações Radicalares: O Método De Barton-mccombieunclassified
“…Forma-se exclusivamente o produto C-5-desoxi 59. Esta seletividade é atribuída à maior estabilidade do radical secundário (em C 5 ) quando comparada a do radical primário (em C 6 ) (Esquema 17) 84,98,99 .…”
Section: Desoxigenações Radicalares: O Método De Barton-mccombieunclassified
“…Barton first demonstrated that tributylstannane-mediated hydrogenolysis of a 2',3'-0-thiocarbonyl derivative of adenosine gave a mixture of 2'-(major) and 3'-deoxy products (20). Analogous reduction of dimeric derivatives of 8 followed by deprotection would produce one equivalent of 2'-deoxynucleoside (7) and one of the parent P-D-xylofuranosyl starting material (5).…”
Section: O W S J Robins Danuta Madej Fritz Hansske John S Wilsmentioning
confidence: 99%
“…The structures of these compounds were established as follows. Firstly 21 was treated with thiocarbonyldiimidazole to give the thionocarbonate 23, which was then reduced with tri-n-butyltin hydride according to the BartonSubramanian procedure (28) to give 22a. The latter was hydrogenated over palladium in the presence of formic acid, and the resulting trio1 22b was acetylated directly to give triacetate 22c.…”
Section: Synthetic Studiesmentioning
confidence: 99%